Arahan Pengembangan Kawasan Permukiman di Kota Tanjungpinang Provinsi Kepulauan Riau - Citra Chintia Dewi; Pavitasari, Andrea Emma; Pribadi, Didit Okta (Jurnal Ilmu Tanah dan Lingkungan, 2023)
Tanjungpinang City is characterized as a coastal area with dense settlements around the port. Based on BPS data, the rate of population growth in the medium category each year causes the formation of new activity centers that are heading towards the mainland. This study aims to: 1) Analyze the pattern of land use change in Tanjungpinang City in 2010-2020; 2) Analyzing land suitability for settlements; 3) Analyzing the availability of land for settlement development; 4) Predict land use; 5) Prepare directions for settlement development in 2030. Land use change analysis is carried out by using the overlay method on land use maps in 2010, 2015 and 2020. The land suitability of residential land is analyzed using the evaluation method developed by FAO 2007. Land availability is carried out by applying some availability criteria. Land use projections for 2030 are made using the Land Change Modeler found in the Terrset application. Based on the results of the study, it was found that there were 6,300.73 ha of land with appropriate land suitability classes and were available based on several criteria. Based on the results of the study also shows that the 2010-2020 period shows that the largest land use change occurs in residential land, in line with this in the prediction of land use in 2030 the largest increase in area also occurs in residential land use. This causes settlements in 2030 to be the largest land use covering an area of ​​3,453.38 hectares or 23.97% of the total area of ​​Tanjungpinang City. The direction of settlement development until 2030 can be focused on lands that are included in priority categories 1 and 2, to avoid disasters, damage to land and land disputes